Borderline personality disorder and childhood trauma: Exploring the buffering role of self‐compassion and self‐esteem. Issue 3 (10th October 2020) - Pohl, Sina; Steuwe, Carolin; Mainz, Verena; Driessen, Martin; Beblo, Thomas
Abstract: Objectives: The aim of the present study was to investigate whether patients with borderline personality disorder (BPD) show lower self‐compassion and self‐esteem than healthy controls and whether patients' self‐compassion and self‐esteem moderate the association between childhood trauma and the severity of their BPD symptoms. Method: Self‐reported self‐compassion, self‐esteem, and the current severity of BPD symptoms were assessed in 35 female patients with BPD and 35 age‐matched control participants. Further, traumatic childhood experiences were recorded in the patient group. Results: Patients with BPD reported significantly lower self‐compassion and self‐esteem compared to healthy controls. In addition, self‐compassion but not self‐esteem moderated the positive correlation between childhood trauma and the severity of BPD symptoms. Discussion: Self‐compassion appears to buffer the negative consequences of childhood traumatization. Therefore, cultivating self‐compassion may be an important therapeutic aim for patients with BPD.